2018
DOI: 10.1007/s13753-018-0176-7
|View full text |Cite
|
Sign up to set email alerts
|

El Niño and the Köppen–Geiger Classification: A Prototype Concept and Methodology for Mapping Impacts in Central America and the Circum-Caribbean

Abstract: The aim of this pilot study conducted by the consortium for capacity building was to develop a prototype concept and methodology for the classification and visualization of the geographic impacts of El Niño on annual climates and seasonality. Our study is based on the Köppen-Geiger climate classification scheme for a set of selected countries affected by strong El Niños in Latin America. By identifying and visualizing the annual and seasonal changes in regional, national, or subnational climate regimes that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…On the other hand, the mid‐latitude climate regime shows a little higher value than the medium effect size (Figure 5, bottom panel ), suggesting the presence of less frequent but longer duration, persistent hydrological droughts in this region. Our findings corroborate previous studies (Gibson et al., 2019; Naranjo et al., 2018; Roundy et al., 2012; Van Loon, 2015), which show precipitation deficit does not necessarily translate into hydrological droughts; land‐atmospheric feedbacks, climate, and catchment control play a vital role in propagating droughts. Further, in mid‐latitudes, a combination of successive dry winter/spring seasons and prolonged soil moisture deficit followed by a lack of groundwater recharge can cause persistent hydrological droughts in slow responding catchments during summer (Hanel et al., 2018; Marsh et al., 2007; Van Loon, 2015).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the mid‐latitude climate regime shows a little higher value than the medium effect size (Figure 5, bottom panel ), suggesting the presence of less frequent but longer duration, persistent hydrological droughts in this region. Our findings corroborate previous studies (Gibson et al., 2019; Naranjo et al., 2018; Roundy et al., 2012; Van Loon, 2015), which show precipitation deficit does not necessarily translate into hydrological droughts; land‐atmospheric feedbacks, climate, and catchment control play a vital role in propagating droughts. Further, in mid‐latitudes, a combination of successive dry winter/spring seasons and prolonged soil moisture deficit followed by a lack of groundwater recharge can cause persistent hydrological droughts in slow responding catchments during summer (Hanel et al., 2018; Marsh et al., 2007; Van Loon, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Our findings are in agreement with the literature that showed that the propagation of droughts in the tropics follows a complex pattern (Van Loon et al., 2014), whereas, in subtropics, a quicker response is apparent from meteorological to hydrological droughts (Gevaert et al., 2018). Subtropical catchments have a relatively stable climate type, such as temperature and precipitation show relatively fewer fluctuations across the year with no sub‐zero temperature and without pronounced seasonal influence (e.g., monsoon) or slowly varying rainfall cycle (Naranjo et al., 2018; Van Loon et al., 2014). This further suggests that catchment characteristics have a relatively lesser role in drought propagation in subtropical catchments than those in the other two climate regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The El Niño phenomenon, which stems from ocean-atmosphere interactions across the equatorial Pacific Ocean, affects regional to local weather patterns every few years (McPhaden et al 2006). El Niño is often associated with water, weather, and climate-related extremes and changes in seasonality (Naranjo et al 2018), that in turn influence local disease ecologies and population exposures (Kovats et al 2003;McGregor and Ebi 2018;Anyamba et al 2019). El Niño's impact on disease transmission occurs directly via ecological changes (for example, hydrology and rising ambient and water temperatures), which may propogate a variety of pathogens, as well as spawn a variety of hydrometeorological (hydromet) hazards, including floods, temperature extremes, windstorms, and droughts.…”
Section: The El Niñ O Factormentioning
confidence: 99%
“…The aim of this study is to explore mapping multi-disease risk during El Niño-Southern Oscillation (ENSO) and hydro-meteorological extremes in northern Peru. It builds on previous climate-health research in South America [1,2] and expands current work on El Niño-related disasters [3,4,5]. ENSO is a climate variability pattern that affects local to global weather patterns every 2 to 8 years.…”
Section: Introductionmentioning
confidence: 96%